Respuestas

2013-05-31T19:39:16+02:00
A. (ax+a)+(5ax-5a)=6b-4a -> ax+a+5ax-5a=6b-4a->6ax-4a=6b-4a->6ax=6b-> 6ax-6b=0
B. (xa+x)-(xa-x)=2a+4-> 0=2a+4
C. x^2-5x+2x-10=x^2-6x-x+6 -> x^2-3x-10=x^2-7x+6 -> 4x-16=0->  x=16/4 -> x=4
¡La mejor respuesta!
  • Koyn
  • Habilidoso Ciencias
2013-05-31T20:03:14+02:00
a(x + 1) + 5a(x - 1) = 2(3b - 2a)
ax+a+5ax-5=6b-4a

6ax=6b-4a-a+5
6ax=6b-5a+5
x=6b/6a-5a/6a+5/6a

B.    x(a + 1) - x(a - 1) = 2a + 4
ax-x-ax+x=2a+4
-2a-4
a=4/-2
a=-2

C.    (x + 2)(x - 5) = (x - 1)(x - 6)
x^2-5x+2x-10=x^2-6x-x+6
x^2-3x-10x^2-7x+6
x^2-x^2-3x+7x=6+10
4x=16
x=16/4
x=4

el primero esta un poko dificil!!!
espero te sirva saludos!!!